(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The eastern Southern Alps are characterized by the superimposition of alpine and dinaric tectonic clcmcnts; the bedrock Of the Friulan plane is composed by structural elements that represent the prosecution of the External Dinarides. This structural setting is the result of the dinaric, alpine and, partly, apenninic tectogeno—sedimentary processes which affected from the Upper Cretaceous to the present an area with peculiar palaeogeographic characters. During the Jurassic—Cretaceous times infact an ’ ’adriatic" carbonatic platform developed with some basins at its- edges: the Belluno, Carnic and Tolmino basins. The authors propose here, on the basis of stratigraphic, tectonic and physiographic elements and with palaeogeographic reconstruction, an evolutionary model of the area that takes in account all these factors, thelr influence and their interactions.